The Influence of Sport Education Model on Responsibility in Basketball Games - Sisi Wulandari; Yudy Hendrayana; Carsiwan Carsiwan (Journal of Physical Education For Secondary Schools, 2021)
This research is behind the low responsibility of students who make the children less able in following the physical educaton lesson. The study also aims to determine and test the influence of Sport Education Model (SEM) on responsibility in basketball games. The methods used in this research are quantitative descriptive. The population in this research is secondary school 1 Cimahi. The samples in this the follow basketball activities amounting to 30 students and no the follow basketball activities amounting to 30 students n. In sampling researchers use purposive sampling techniques. This research uses instruments such as responsibility questionnaire and interview. The results showed that Sport Education Model (SEM) provides a significant influence on responsibility in basketball games.